Undergraduates' Experiences with Online and in-Person Courses Provide Opportunities for Improving Student-Centered Biology Laboratory Instruction - Mark A. Sarvary; Frank R. Castelli; Mitra Asgari (Journal of Microbiology & Biology Education, 2022)
ABSTRACT Biology laboratory courses with hands-on activities faced many challenges when switched to online instruction during the COVID-19 pandemic. The transition back to in-person instruction presents an opportunity to redesign courses with greater student input. Undergraduates in an ∼350-student laboratory course were surveyed about their preferences for online or in-person instruction of specific laboratory course components. We predicted that students who have taken a virtual laboratory course prefer keeping some of the components online. We also hypothesized that their preferences are affected by their experience with online-only or with both online and in-person instruction. The results showed that students would like to move the laboratory component and group meetings back to in-person instruction, even if they never experienced college-level in-person courses. Also, many components, including the lectures, exams, assignment submission, and office hours are preferred to be held online. Surprisingly, students who have only taken online courses would rather give group presentations in person, while those who experienced both online and in-person instruction were undecided. Group presentations were the only component where the preference of the two groups significantly differed. Self-assessed learning gains showed that students performed very well in both the online semesters and the in-person semesters. Therefore, the preferences measured in this study were likely developed based on students’ future expectations and personal gains, and not only on their metacognitive decisions and academic performances. This study provides considerations for redesigning components of laboratory courses to be more student-centered after the pandemic.